(untitled) (Economic and Political Thought, 2015)
Transformations of the international environment we are facing nowadays, force the EU to verify its policy on the international arena. The Russian- Ukrainian conflict and a huge wave of immigrants from the war-affected areas of the Middle East (especially Syria) require the development of a new strategic approach by the Union. The previous EU assumptions formulated in the European Security Strategy (ESS) and in the detailed strategies (regional, topic-based and those relating to defence) seem to be inadequate to deal with the current situation not only in the direct neighbourhood of the EU but also outside it. The aim of the article is to verify the assumption that the European Union needs a profound change of the model of its foreign policy. The basis of this shall be a newly defined global strategy of foreign policy of the EU, w hich would at the same time address contemporary challenges and dangers. In order to verify this thesis, the introductory analysis of the previous EU strategies in the international relations (the instruments and policy in external relations) shall be made; moreover, the conditions and bases for the formulation of a new strategic model need to be discussed. And finally, the EU foreign policy in chosen framework areas should be revised as well as recommendations for the future EU foreign policy should be made.